2008
DOI: 10.1016/j.oraloncology.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal imbalances in oral squamous cell carcinoma: Examination of 31 cell lines and review of the literature

Abstract: Classical and molecular cytogenetic analysis, including fluorescence in situ hybridization (FISH) and chromosomal comparative genomic hybridization (CGH), were used to examine genetic changes involved in the development and/or progression of oral squamous cell carcinoma (OSCC). Of 31 OSCC cell lines studied, more than one-third expressed clonal structural abnormalities involving chromosomes 3, 7, 8, 9, and 11. Eleven OSCC cell lines were evaluated using CGH to identify novel genome-wide gains, losses, or ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
74
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 79 publications
2
74
0
7
Order By: Relevance
“…Cytogenetic analyses in conjunction with molecular genetics analyses by a number of research groups have shown an accumulation of genetic abnormalities during the development and/or progression of OSCC (23). In this study, we identified 11 downregulated genes, CRISP3, SCGB3A1, AGR2, PIP, C20orf114, TFF1, STATH, AZGP1, MUC7, DMBT1 and LOC389429, and 2 up-regulation genes, LNM, lymph node metastasis confirmed by histopathological examination within the 12-month follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic analyses in conjunction with molecular genetics analyses by a number of research groups have shown an accumulation of genetic abnormalities during the development and/or progression of OSCC (23). In this study, we identified 11 downregulated genes, CRISP3, SCGB3A1, AGR2, PIP, C20orf114, TFF1, STATH, AZGP1, MUC7, DMBT1 and LOC389429, and 2 up-regulation genes, LNM, lymph node metastasis confirmed by histopathological examination within the 12-month follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…39 However, a sex link was dubious; the loss of the short arm of the Xi was a common observation in females and Y loss was observed in about 50% of males. 39 In HNSCC cases, Xi reactivation can potentially be considered a marker of heterochromatin instability associated with poor prognosis as, much like cervical cancer, the disease may be associated with epigenetic modifications as well as oncoviruses that could alter the X-linked genes. 11,36,37 Thus, the destabilised genomic repertoire in HNSCC appears to be further undermined by epigenetic events.…”
mentioning
confidence: 99%
“…11,36,37 Thus, the destabilised genomic repertoire in HNSCC appears to be further undermined by epigenetic events. 39,40 However, before considering an association between the Barr body and HNSCC, a causal relation between X-linked TSGs and HNSCC development must be established. A summary of the X-linked genes involved in HNSCC development and their various loci, functions and mechanisms can be found in Table 1.…”
mentioning
confidence: 99%
“…De forma abrangente, análises citogenéticas e genéticas moleculares em carcinoma epidermóide de boca revelaram perdas cromossômicas em 3p, 4p, 8p, 11q, e 18q, e ganhos em 3q, 5p, 7p/q, 8q, 9q, 11q, 14q, 19q, e 20q (GOLLIN, 2001;JIN et al, 1995;JIN et al, 2006a;LESE et al, 1995;MARTIN et al, 2008;SPEICHER et al, 1995;WREESMANN;). Uma vez que alterações cromossômicas numéricas e estruturais são responsáveis pelo acúmulo de aberrações genéticas que conduzem ao desenvolvimento e progressão tumoral (SAUNDERS et al, 2000), Weber et al (1998) MARTIN et al, 2008).…”
Section: Carcinoma Epidermóide De Bocaunclassified
“…No câncer da região de cabeça e pescoço, as mais frequentes envolvem ganhos em 3q, 8q, 9q, 20q, 7p, 11q13, e 5p e perdas em 3p, 9p, 21q, 5q, 13q, 18q, e 8p (GOLLIN, 2001). A região cromossômica 11q13 foi descrita como alterada em diferentes neoplasias, inclusive em carcinomas epidermóides de boca MARTIN et al, 2008 -7). A escolha desses genes para validação por qRT-PCR (reação em cadeia da polimerase quantitativa precedida de transcrição reversa) em um grupo amostral maior se fez necessária no intuito de legitimar a utilidade desses genes como marcadores moleculares no carcinoma epidermóide de boca.…”
Section: Introductionunclassified